The Effectiveness of Internet-based Multimedia Assisted Language Learning (IB-MALL) in Improving Students’ English Proficiency under Sino-foreigner Cooperative Education Context From Students’ Perspectives - Liu, Qirui (2019)
This empirical study is intended to explore the effectiveness of Internet-based Multimedia Assisted Language Learning (IB-MALL) under the Sino-foreign cooperative education context from students’ perspectives in China. With the expansion of the globalization and development of technology, there are more and more pedagogical experiments of applying the internet and multimedia being carried out in the education field. However, in China, there are limited foci on the unique context of Sino-foreign cooperative education, in which non-English major students are facing challenges of their unqualified English proficiency. Therefore, it is well worth exploring the effectiveness of IB-MALL on those groups of students. This study adopted both qualitative and quantitative approaches. Two questionnaires including both multiple choices and open-ended questions were designed and given to the students to collect their self-evaluation of learning outcomes and attitudes toward IB-MALL. Based on the findings, most of the students suggested that their overall English proficiency has been improved, as well as other skills. In terms of attitudes, almost all the students showed a positive acceptance and preference for the IB-MALL. Meanwhile, students also made suggestions for the future application of IB-MALL.